Analisis Terhadap Faktor Penyebab Tingkat Perceraian Di Pengadilan Agama - Heri Tahir; Andi Aco Agus; Ni’matul Aliyah Fajri Utari (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2024)
Abstract: This study aims to determine (1) The factors causing the divorce rate in the jurisdiction of the Watansoppeng Religious Court. (2) The strategy adopted to overcome the divorce rate in the jurisdiction of the Watansoppeng Religious Court. In this research, the research approach used is qualitative research with a qualitative descriptive research type. The data sources used are primary data sources and secondary data sources. Data collection techniques include interviews and documentation. Triangulation and member checking are used as procedures to check the validity of the data, as well as using data reduction, data presentation, and drawing conclusions as data analysis techniques. The results of the research show; (1) The factors causing the divorce rate in the jurisdiction of the Watansoppeng Religious Court are based on 13 factors or reasons for divorce which are grouped, namely; the factors of moral decadence are classified as: drunkenness, madness and gambling. Factors of household neglect are classified as: leaving one of the parties, domestic violence, and economics. Factors being sentenced to prison, polygamy, physical disability, constant disputes and quarrels, and forced marriage. (2) The strategy adopted to overcome the divorce rate in the jurisdiction of the Watansoppeng Religious Court is; First, providing outreach to the public about the importance of knowledge of legal and religious observance regarding marriage and divorce. Second, mediation in the Religious Court is the final strategy carried out with the aim of reconciling husband and wife who want a divorce.